2003
DOI: 10.1128/mcb.23.4.1390-1402.2003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cross-Antagonism between Transcription Factors FLI-1 and EKLF

Abstract: FLI-1 is an ETS family transcription factor which is overexpressed in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
108
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 81 publications
6
108
0
2
Order By: Relevance
“…[35][36][37] FLI-1 has also the ability to inhibit the erythroid differentiation in several erythroleukemic cell lines. [38][39][40] Altogether, these data strongly suggest that during normal hematopoiesis, FLI-1 not only activates the MK differentiation program but also simultaneously represses the erythroid program. In favor of this hypothesis, it was recently reported that FLI-1 knock-out induces a blockage in MK differentiation 33,34,41 with an expansion of erythroid progenitors.…”
Section: Discussionmentioning
confidence: 71%
“…[35][36][37] FLI-1 has also the ability to inhibit the erythroid differentiation in several erythroleukemic cell lines. [38][39][40] Altogether, these data strongly suggest that during normal hematopoiesis, FLI-1 not only activates the MK differentiation program but also simultaneously represses the erythroid program. In favor of this hypothesis, it was recently reported that FLI-1 knock-out induces a blockage in MK differentiation 33,34,41 with an expansion of erythroid progenitors.…”
Section: Discussionmentioning
confidence: 71%
“…The generation of the bipotential megakaryocyte/erythroid progenitors progenitor arises from the loss of PU.1 with the ensuing process of erythrocytic versus megakaryocytic commitment dependent upon the EKLF and Fli-1 transcription factors, respectively. 68 Although the precise mechanism of how EKLF and Fli-1 can direct lineage commitment remains to be determined, recent studies have shown the EKLF-mediated repression of megakaryopoiesis by the inhibition of Fli-1 recruitment to megakaryocytic-specific promoters as well as to its own promoter. 69 Based on these observations, mutual cross-antagonism between transcription factors is a common and re-occurring mechanism in regulating cell fate choices during hematopoiesis.…”
Section: Pu1 and Gata-1 Interact During Early Hematopoietic Cell Decmentioning
confidence: 99%
“…This may result in inhibition of an intrinsic but non-cell autonomous retinoblastoma function required for terminal erythroid differentiation (47). Alternatively, a direct interference of FLI-1 with other transcriptional regulators important for erythroid differentiation such as retinoid/thyroid nuclear hormone receptors and EKLF has been proposed (8,9).…”
Section: Fli-1 In Erythroblast Transformationmentioning
confidence: 99%
“…However, in the context of specific promoters, FLI-1 binding results in transcriptional repression through ill defined mechanisms (6,7). In addition to its transcriptional regulatory properties resulting from its tethering to DNA, FLI-1 has been shown to modulate in trans the activity of other unrelated transcriptional regulators through protein-protein interactions (8,9).…”
mentioning
confidence: 99%